2017
DOI: 10.1371/journal.pone.0172104
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for care towards the end of life when decision-making capacity may be impaired: A large scale cross-sectional survey of public attitudes in Great Britain and the United States

Abstract: BackgroundThere is continuing public debate about treatment preferences at the end of life, and the acceptability and legal status of treatments that sustain or end life. However, most surveys use binary yes/no measures, and little is known about preferences in neurological disease when decision-making capacity is lost, as most studies focus on cancer. This study investigates changes in public preferences for care towards the end of life, with a focus on measures to sustain or end life.MethodsLarge-scale inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
5
13
0
Order By: Relevance
“…For logistic regression analysis of the general public, we used the following six independent variables based on previous reports and discussion among the authors of this study [15,21,22]: gender (reference: male), age < 64 years, education (reference: junior high or high school), living with family, death of a close person in the past 5 years, and presence of a family doctor.…”
Section: Discussionmentioning
confidence: 99%
“…For logistic regression analysis of the general public, we used the following six independent variables based on previous reports and discussion among the authors of this study [15,21,22]: gender (reference: male), age < 64 years, education (reference: junior high or high school), living with family, death of a close person in the past 5 years, and presence of a family doctor.…”
Section: Discussionmentioning
confidence: 99%
“…In general, internal states, such as values and outlooks emerged as better predictors than background information. Studies of the general public regarding preferences for care under specific scenarios [28,29] found that preferences were affected by previous personal experience, religiosity, and age, as well as by the anticipated scenario under which EoL decisions are to be made.…”
Section: Plos Onementioning
confidence: 99%
“…Within the United States, there is oftentimes a focus on litigation to resolve issues of conflict, which fuels fearful attitudes and defensive medicine. Issues such as the use of medical marijuana and assisted dying are controversial globally (Clarke et al., ; Compton, Volkow, & Lopez, ).…”
Section: Society Politics and The Economymentioning
confidence: 99%